2020
DOI: 10.1177/0363546520958708
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Superior Capsular Reconstruction With Mesh Augmentation for the Treatment of Irreparable Rotator Cuff Tears: A Comparative Study of Surgical Outcomes

Abstract: Background: Arthroscopic superior capsular reconstruction (ASCR) is an alternative to open surgery for irreparable chronic rotator cuff tears (RCTs). This approach can provide static restraint while avoiding upward migration of the humeral head. However, graft tears and their effect on clinical outcomes after ASCR remain a debated topic. Purpose: To evaluate the clinical outcomes of ASCR with mesh augmentation for the treatment of irreparable RCTs. Study Design: Cohort study; Level of evidence, 3. Methods: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 58 publications
2
62
0
1
Order By: Relevance
“…(1) Severe bone deformity (Hamada grade 5) (2) Severe superior migration of the humeral head that could not be corrected using manual arm traction during diagnostic arthroscopy (3) Irreparable subscapularis tendon (4) Cervical nerve and axillary nerve palsy (5) Previous rotator cuff surgery (6) Revision of the ASCR (7) \2 years of minimum follow-up (8) Patient died of an unrelated cause ASCR was performed between January 2013 and September 2016, and ASCR using mesh augmentation was performed between October 2016 and June 2020. 24 The modification of the surgical technique was made arbitrarily by the operating surgeon based on the observation of the preliminary result. 24 ASCR was performed for patients in relatively good general condition based on the American Society of Anesthesiologists physical status classification (grade, \3) disregarding chronologic age.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Severe bone deformity (Hamada grade 5) (2) Severe superior migration of the humeral head that could not be corrected using manual arm traction during diagnostic arthroscopy (3) Irreparable subscapularis tendon (4) Cervical nerve and axillary nerve palsy (5) Previous rotator cuff surgery (6) Revision of the ASCR (7) \2 years of minimum follow-up (8) Patient died of an unrelated cause ASCR was performed between January 2013 and September 2016, and ASCR using mesh augmentation was performed between October 2016 and June 2020. 24 The modification of the surgical technique was made arbitrarily by the operating surgeon based on the observation of the preliminary result. 24 ASCR was performed for patients in relatively good general condition based on the American Society of Anesthesiologists physical status classification (grade, \3) disregarding chronologic age.…”
Section: Patient Selectionmentioning
confidence: 99%
“…24 The modification of the surgical technique was made arbitrarily by the operating surgeon based on the observation of the preliminary result. 24 ASCR was performed for patients in relatively good general condition based on the American Society of Anesthesiologists physical status classification (grade, \3) disregarding chronologic age. 10,29 A total of 73 patients were included in the present study for analysis.…”
Section: Patient Selectionmentioning
confidence: 99%
“…3 The timing of graft tear was categorized as early (within 3 months postoperatively), midterm (at 3-6 months postoperatively), and late (after 6 months postoperatively). 24 The acromiohumeral distance (AHD) was measured using plain standard shoulder radiographs, which were taken with the radiographic beam tilted 20° caudally in anteroposterior projection. 58 The stage of rotator cuff arthropathy was evaluated using the Hamada classification system.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, other surgical groups have also reported the results of autograft SCR, often with their own modifications. 2,3,12,16 Azevedo et al, 2 for example, utilized a fascia lata autograft harvested with a minimally invasive technique. Kholinne et al 12 reported that reinforcing a fascia lata autograft SCR with polypropylene mesh yielded improved results in graft integrity and several clinical parameters.…”
mentioning
confidence: 99%
“…2,3,12,16 Azevedo et al, 2 for example, utilized a fascia lata autograft harvested with a minimally invasive technique. Kholinne et al 12 reported that reinforcing a fascia lata autograft SCR with polypropylene mesh yielded improved results in graft integrity and several clinical parameters. Barth and colleagues 3 have described their experience utilizing the native long head biceps tendon in lieu of fascia lata for massive posterosuperior rotator cuff tears.…”
mentioning
confidence: 99%